(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article contains an analysis of noise protection measures, a histogram of the impact of noise on buildings around the main busy street and roads. Instructions were given to reduce the noise on the streets and roads of Samarkand city.